(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Entrepreneurship plays an important role in the sustainable development of the national economy and plays a leading role in solving economic and social problems. In our country, a number of tasks were carried out in the directions of creating an entrepreneurial environment in every family, providing them with financial support, and providing preferential loans. This article examines the activity of banks on the use of preferential loans allocated for the organization of entrepreneurship in each family, and presents analytical data, suggestions and recommendations.